A Renegade View Of What We Do - Don E. Wells (Journal of Applied Communications, 1979)
When I went to Washington in the fall of 1977 to work on a nine-month special assignment with Mason Miller in USDA, it was not my intent to become a resident critic of the Land-Grant/USDA agricultural and home economics information system.